Mitigating Risks Associated with Secondary Intravenous (Iv) Infusions: An Empirical Evaluation of a Technology-Based, A Practice-Based, And a Training-Based Intervention - Chan, Katherine Y.; Pinkney, Sonia; Fan, Mark; Colvin, Chris; Easty, Tony; Trbovich, Patricia (CMBES Proceedings, 2013)
Multiple intravenous (IV) infusions are commonly used in the clinical setting to administer numerous fluids and medications to patients. Secondary infusion, also known as piggyback infusion, is a specific multiple IV infusion setup to deliver intermittent medications. Errors related to the setup and administration of secondary infusions have led to patient safety concerns[1, 2]. However, there is currently no study that specifically aims to empirically test the effects of interventions on the safety of secondary infusions in the clinical setting. The objective of this experimental study was to empirically evaluate interventions that may reduce errors during the administration of secondary infusions. Three mitigating strategies (a technology-based, a practice-based, and a training-based intervention) were tested. Forty critical care nurse participants performed secondary infusion tasks in a high-fidelity simulated clinical environment, with and without interventions. The types and frequency of errors were collected. The effects of the interventions on workflow and the reduction of secondary infusion errors were investigated.